An analysis of organisational factors related to affective organisational commitment of Secondary school teachers in Mashonaland Central Province of Zimbabwe - Kasowe, Rittah (IJRDO- Journal of Educational Research, 2017)
Performance of secondary school pupils accelerated in a declining manner since 1984 to date. Although much has been done to improve conditions of the teacher since the teachers are at the helm of students learning, students’ performance has continued to decline. Despite training obtained from teachers colleges, what is contributing to their effectiveness has not been well researched. Affective organisational commitment of secondary school teachers in Zimbabwe still remain an inadequately researched area. Whereas teachers could be motivated by employers, the gendered outcomes of their commitment to the organisation especially on their affective commitment has not been adequately investigated. The primary purpose of the study was to make a critical analysis of variables and factors contributing to affective organisational commitment using Stufflebeam (2007)’s Context Input Process and Product decision facilitation model of evaluation approach. The approach specified the imbalances in each phase of evaluation focusing on, organisational factors, how each factor contributed to affective organisational commitment of secondary school teachers. The study used statistical tests of multiple regression analysis and step wise regression analysis on quantitative survey data obtained from Affective organisational commitment. The quantitative data were gathered using two seven point Likert scales ranging from strongly agree to strongly disagree. A statistical program SPSS was used to investigate the relationships among variables in the research model. Regardless of the types of dependent or independent variables, linear multiple step wise regression analyses were performed in order to find out the significance of the variables. This was supplemented by qualitative data gathered and addressing organisational factors. The qualitative data were collected using semi structured face to face interviews and focus group discussions in order to triangulate the evidence obtained from quantitative data. The qualitative data were analysed using NVIVO to come up with themes. Thus this study used a mixed methodology approach. The study established that factors such as; occupational status, management worker relationship, recognition, variety in the profession, opportunity to use ability and subject specialisation, were strong determinants of affective organisational commitment related to secondary teachers’ affective organisational commitment and impacting negatively on pupils’ and schools’ performance. The study recommended that Educational planners must involve teachers in policy decision making at all levels, provide support and staff development workshops. Future researchers might wish to expand on studies that indicate a connection between factors established and the degree of pupils’ performance.